Fruit quality in "Cripp's Pink" apple, especially colour, as affected by preharvest sprays of aminoethoxyvinylglycine and ethephon - Whale, Suparna; Singh, Zora; Behboudian, Hossein; Janes, Albert; Dhaliwal, Satvinder (Elsevier, 2008)
'Cripp's Pink' apple grown in Western Australia often develops poor colour at commercial harvest resulting in economic losses. To determine if fruit colour could be improved without advancing ripening, 'Cripp's Pink' apple fruit on trees were sprayed with aminoethoxyvinylglycine (AVG) alone, ethephon alone, or AVG followed by ethephon. The experiments were conducted at two different locations in Western Australia in 2002 and 2003. Fruit sprayed with AVG alone had retarded colour development at harvest. However, ethephon applied after AVG enhanced percent red blush, anthocyanin concentration and reduced chlorophyll concentration in the fruit skin in both locations. These fruit had similar colour to those treated with ethephon alone. Internal ethylene concentration and fruit firmness were unaffected by the different treatments in 2002. However, in 2003 AVG with or without ethephon reduced internal ethylene concentration and maintained firmness compared to ethephon alone. In conclusion, AVG treatment alone delayed colour development and ripening of 'Cripp's Pink', while AVG application 5 weeks before harvest followed by an ethephon application 2 weeks later enhanced red colour at commercial harvest. This is, therefore, an effective tool for improving colour of 'Cripp's Pink' apples at commercial harvest without adversely affecting other fruit quality attributes.